Auctions vs. Negotiations: The Case of Favoritism - Achim Wambach; Vitali Gretschko (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We compare two commonly used mechanisms in procurement: auctions and negotiations. The execution of the procurement mechanism is delegated to an agent of the buyer. The agent has private information about the buyer s preferences and may collude with one of the sellers. We provide a precise definition of both mechanisms and show contrary to conventional wisdom that an intransparent negotiation yields a higher buyer surplus than a transparent auction for a range of parameters. In particular, for small expected punishments there exists a lower and an upper bound on the number of sellers such that the negotiation yields a higher buyer surplus with a probability arbitrary close to 1 in the parameter space. Moreover, if the expected punishment is small, the negotiation is always more efficient and generates a higher surplus for the sellers.
Keywords: D44; D73; H57; 330